Economic Survey of Latin America and the Caribbean 1996-1997 - Economic Commission for Latin America; the Caribbean (United Nations, 1997)
In 1996 and 1997, the economies of Latin America and the Caribbean appeared to have returned to the pattern of moderate growth. Part I of this publication gives insight into the economic trends, the international economy and the role of exchange rate policy in the region. Part II explores the economic developments by country. Included also is a statistical annex on diskette, which contains tables extending as far back as 1980.